Answer:
The completed slope point equation is [tex]y=3x+23[/tex]
Step-by-step explanation:
Given points are (-8,-1) and (-6,5)
Now to find the slope with these points
[tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
Let [tex](x_{1},y_{1})[/tex] and [tex](x_{2},y_{2})[/tex] be the points (-8,-1) and (-6,5) respectively
Substitute all values in [tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex] we get
[tex]m=\frac{5-(-1)}{-6-(-8)}[/tex]
[tex]=\frac{5+1}{-6+8}[/tex]
[tex]=\frac{6}{2}[/tex]
[tex]=3[/tex]
Therefore m=3
Now to find the equation:
[tex]y-y_{1}=m(x-x_{1})[/tex]
Let [tex](x_{1},y_{1})[/tex] be the point (-6,5)
Substitute the point (-6,5) and slope m=3
[tex]y-5=3(x-(-6))[/tex]
[tex]y-5=3(x+6)[/tex]
[tex]y-5=3x+18[/tex]
[tex]y=3x+18+5[/tex]
[tex]y=3x+23[/tex]
Therefore the completed slope point equation is [tex]y=3x+23[/tex]